Modeling of blood cell surface oscillations as fluid-filled multilayer viscoelastic shells - Батюк, Л. В.; Кізілова, Н. М. (Київський національний університет імені Тараса Шевченка, 2022)
Rheological properties of the red blood cells (RBC) determine their movement in the larger and smaller blood vessels, oxygen and carbon dioxide delivery to/from the cells. Those properties vary significantly with age and health state of an organism. In this paper a new rheological model of RBC as a thin multilayer shell, which includes the cytoskeleton, lipid bilayer, glycocalyx, and hydrate shell as Maxwell's viscoelastic bodies is proposed. Mechanical properties of the rheological model in isotonic, isometric and dynamic experiments are studied. The oscillations of the surfaces of erythrocytes or other cells in the approximation of multilayer viscoelastic shell filled with a viscous fluid are investigated. The expressions for the dynamic Young’s modules and viscosity/fluidity coefficients as functions of the viscoelastic and geometric parameters of the layers are obtained. The problem of propagation of small perturbations along the cell surface is considered. The solutions of the problem in the form of Young and Lamé waves are obtained. The method of identification of the erythrocyte parameters from the experimental measurements of the wave propagation on the basis of the developed mathematical model for the purposes of clinical diagnostics of diseases with use of a microdrop of blood of the patient is proposed. Pages of the article in the issue: 40 - 43 Language of the article: Ukrainian
Keywords: Erythrocytes; Mathematical modeling; Multilayer shells; Free oscillations; Forced oscillations; Еритроцити; Математичне моделювання; Багатошарові оболонки; Вільні коливання; Вимушені коливання